IMPACT OF THE EXTERNAL AUDITOR’S EFFECTIVENESS ON THE FINANCIAL REPORTING QUALITY: THE MEDIATING EFFECT OF AUDIT QUALITY - Wan Anisah, Endut; Nik Mohd Norfadzilah, Nik Mohd Rashid; Hamza Kamel, Qawqzeh; Mohammad Mustafa, Dakhlallh (2020)
The main purpose of this study is to investigate the influences of the external auditor's effectiveness on the financial reporting quality, as well as the mediating effect of the external audit quality on this relationship in the Jordanian firms. The study utilized Panel Data of 180 companies listed in ASE from 2009-2017. The data were analyzed using the Causal Steps Method. The results revealed that the auditor size has an insignificant impact on FRQ, whereas the industry specialization has significantly a positive impact on FRQ through preventing the EM practices, as well as the auditor tenure has significantly a negative impact on FRQ. The results also revealed that the auditor size has a negative influence on the audit quality, the industry specialization, and the auditor tenure as the factors that positively and significantly affect the audit quality. Regarding the mediation effect, the results indicated that the relationship between the auditor's effectiveness and FRQ is partially mediated by the audit quality (fees). The findings are important for the shareholders, auditors, regulatory bodies and decision-makers in introducing new legislations for the audit profession, encouraging specialization in industry, and supporting the external auditor rotation regulations in the Jordanian firms. The current study is considered the first study that addresses the relationship between the effectiveness of the external auditor and both the audit quality and FRQ, and the mediating effect of the audit fees on these relationships in the Jordanian context.